Nexus between despotic leadership style and employee’s well-being: A case of a Telecommunication Company in Ghana - Sarpong, Daniel Agyemfour-Agyemang; Aniah, Emelia; Amankwah, Nana Yaa; Bediako , Isaac Asare (Annals of Human Resource Management Research, 2025)
Purpose: This study examined the influence of despotic leadership style on the various dimensions of employee well-being (psychological, physical, interpersonal, environmental, and total well-being) in an XT Telecommunication Company in the Greater Accra Region of Ghana. Methodology/approach: Quantitative research approach was adopted for this study. The study employed the use of census sampling technique. The population for this study was the entire workforce of 150 employees of XT Telecommunication Company in Ghana. Data was collected through standardized structured questionnaire. Data received was analysed through structural equation modelling using Smart PLS 3.0 statistical program. Results/findings: The findings revealed that despotic leadership style positively influenced employees’ psychological and physical well-being. Additionally, findings reveal a positive association between despotic leadership and interpersonal, environmental, and overall well-being. Conclusion: These findings highlight the context-specific nature of leadership outcomes and challenge the universal assumption that despotic leadership is detrimental to employee welfare. Limitations: This includes the specificity to Ghanaian society, which may reduce the generalizability of findings across different cultural settings. Future research should explore cross-cultural comparisons and longitudinal impacts to deepen understanding of despotic leadership’s diverse effects on employee well-being. Contribution: The study contributes to leadership and organizational behavior literature by highlighting the nuanced role of cultural context in shaping leadership outcomes, thereby broadening theoretical and practical understandings of leadership effectiveness.